20 The masterclass series in family doctor leadership: evaluation of a new approach to leadership development. (3rd November 2019) - White, David; Glazier, Rick; Martin, Danielle; Shapiro, Marla; Whitehead, Cynthia; Crann, Sara; Carroll, June; Freeman, Risa; Kidd, Michael
Abstract : Context: Leadership is essential for quality improvement in family medicine. Objective: To assess whether the Master Class approach to developing 'rising stars' in performing arts is effective in developing emerging leaders in academic family medicine. Design: Mixed Methods, combining quantitative evaluation of five sessions and qualitative assessment of participants' pre-course assignments and post-course interviews. Setting: The Department of Family & Community Medicine (DFCM) at the University of Toronto, comprising 14 academic sites, multiple community practices and over 1, 700 faculty.Participants: Sixteen 'rising star' DFCM leaders, identified by site Chiefs and Program Directors. Intervention: Five 2-hour evening sessions over ten weeks, each conducted by a different DFCM facilitator with internationally recognized leadership in varied domains. Outcome measures: Qualitative assessment of pre-course descriptions by participants of one of their current challenges, quantitative ratings of each session and qualitative assessment of impact on participants. The problem descriptions and interviews were assessed using descriptive thematic analysis. Results: The participants' descriptions of their leadership challenges revealed significant variation in level of complexity, scope, and framing of the issues. Evaluations of individual sessions were uniformly high, yielding a combined average of all elements of 4.72/5. Analysis of participant interviews at 2–4 months post-course revealed the following themes: impact or potential for impact on their work; most effective aspects; least effective aspects; participant expectations; suggestions for improvement; impact on self-perception as leaders; broader perceptions of leadership approaches; and acquisition of specific skills. Conclusion: The Master Class approach can be adapted to developing rising leaders in family medicine and may be broadly applicable to healthcare leadership development.